Teachers’ Role in Overcoming Racial Discrimination in Elementary Schools: Peran Guru dalam Mengatasi Diskriminasi Rasial di Sekolah Dasar - Azmi Riadi; Apdoludin; Dedek Helida Pitra (Academia Open, 2025)
Background (General): Racial discrimination in schools continues to hinder inclusive education, affecting students’ psychological, social, and academic growth. Background (Specific): In Indonesia’s multicultural setting, primary schools must implement national policies such as Kurikulum Merdeka and the Profil Pelajar Pancasila to foster tolerance and diversity, yet evidence from classroom practices remains limited. Knowledge Gap: While existing studies explore multicultural education, few provide empirical insights into how elementary school teachers address racial discrimination in real classroom interactions. Aim: This study investigates the role of teachers in preventing and mitigating racial discrimination at SD Negeri 100/II Muara Bungo, highlighting their strategies and challenges. Results: Findings show that teachers embed tolerance values in lessons, use personal approaches to support minority students, and foster collaborative, diversity-oriented classroom activities. However, they face barriers such as limited training, lack of systemic school support, and external social stereotypes. Novelty: The study uniquely combines empirical field data with the framework of national education reforms, offering localized strategies rooted in cultural practices and values of Pancasila. Implications: Strengthening teacher training, institutional policies, and whole-school collaboration is essential to building sustainable, inclusive learning environments that reduce racial discrimination from the earliest stages of education.Highlight : Teachers play a vital role in instilling values of tolerance in elementary schools. Key challenges include limited training and lack of institutional support. A whole-school approach is needed to create an inclusive environment. Keywords : Role of Teachers, Racial Discrimination, Elementary School, Inclusive Learning, Tolerance